Efficacy of growth hormone supplementation with ultrashort GnRH antagonist in IVF/ICSI for poor responders; randomized controlled trial - Ehab H. Mohammad; Ahmed G. Abou El Serour; Eman A.H. Mohamed; Amr H. Abbasy; Mahmoud Zaatar; Kamal A. Rageh; Mohamed M. Shafeek; Emad R. Issak (Elsevier, 2021)
Objectives: To compare the ICSI-ET outcomes in poor responders who underwent ovarian stimulation by the ultrashort GnRH antagonist protocol with or without adjuvant GH injection. Material and methods: This randomized controlled study was conducted at Al-Azhar University from December-2018 to June-2019 upon 156 participants. All patients received the same preparations. After randomization, in the study group, women have received GH 4 IU/day subcutaneous injection from the second day of the cycle stopped one day before ovum pickup. While in the control group, women have received subcutaneous saline in the same dosing as in the study group. After intervention, all procedures were the same in both groups. The main outcome measure was the clinical pregnancy rate. Statistical analysis was based on the intention-to-treat population. Results: Both groups were comparable with regard their baseline characteristics (p-values > 0.05). Ovulation characteristics were comparable (p-values > 0.05). The level of E2 is significantly (p-value = 0.003) higher in the GH group. The oocyte retrieved number was significantly (p-value < 0.001) higher in the GH group 4.94 ± 1.77 than in the control group 3.74 ± 1.82. The mean number of MII oocytes was significantly (p-value < 0.001) higher in the GH group 3.3 ± 1.36 than in the control group 2.29 ± 1.24. Fertilization characteristics, implantation rate, pregnancy rate were comparable (p-values > 0.05). Conclusion: Despite the fact that this study showed no significant increase in the clinical and chemical pregnancy rates by the addition of GH to the ultrashort antagonist protocol in poor responders, the number of retrieved oocytes was significantly higher in the GH group. Clinical trial registration: ClinicalTrials.gov Identifier: NCT03759301.